(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Mastering any skill, including communication skills, comes down to practice. By practicing speaking, you can learn from mistakes and build both your vocabulary and understanding. Speech training is one of the most interesting and useful parts of learning English.